The Role Of Climate And Population Density In The Spread Of Dengue Fever: A Spatial Analysis Of Padang City 2022–2024 - Hikmi, Nailul; Gusti, Aria (Preventia: The Indonesian Journal of Public Health, 2025)
In 2023, Padang city had a dengue fever incidence rate of 46.5 per 100,000 population, an increase compared to the previous year. Climate change, with the transition from the dry to the rainy season, contributed to a surge in dengue fever cases. This study aims to determine the relationship between environmental factors and the incidence of dengue fever in Padang City from 2022 to 2024. This study uses an ecological study design with a sample of all dengue fever cases recorded by the Padang City Health Office. Climate data was obtained from the Indonesian Agency for Meteorological, Climatological, and Geophysical (BMKG), and population density from Statistics Indonesia (BPS), recorded from January 2022 to December 2024. Data analysis included univariate and bivariate analyses, Spearman's correlation test, and spatial analysis. The results showed that DHF cases in Padang City increased from July to October. Bivariate results showed that air temperature (r =- 0.148), rainfall (r = 0.162), and sunshine duration (r = 0.270) were correlated with DF cases. Spatial analysis revealed an inconsistent relationship between DHF cases and population density. It is hoped that the health department will increase DHF prevention efforts, such as the 3M Plus program, before rainfall increases from September to December.